The preacher's daughter eaudiobook Annie's people series, book 1. - Lewis, Beverly (Annie's People, 2006)
New York Times and USA Today best-selling Christian novelist Beverly Lewis continues her tradition of Amish stories with the Annie's People series. In the first book, Lewis addresses young Annie Zook's inner conflict between the strong bonds of her family and faith and the allurement of her talent. Her love of drawing has thus prevented her from choosing a husband, much to her Old Order preacher father's consternation. Annie's feelings grow further convoluted when her longtime pen pal from the outside world Louisa Stratford comes to visit and encourages her to cultivate her gift.